Usability of QR menus: addressing the recomendations against COVID-19 - Piñón Vargas, Mauricio (2020)
The usability of the QR codes is measured in a well-known cafeteria in the city of Puebla, Mexico, following the guidelines of the Government of Mexico which recommend the food and beverage sector to eliminate physical menus as they are considered a point of spread of COVID-19 and its replacement by digital menus distributed by QR codes.     The methodology in this research is that of a case study using a real environment. The ease of use of the menu by diners and employees of the establishment is measured. The results are oriented to the use of this technology as an option to reduce contact surfaces and at the same time it is novel for users; however, there are still gaps in terms of available peripherals and Internet speed.